Anesthesia Technique Selection Pattern in Patients Undergoing Lower Extremities Surgery at Dr. Hasan Sadikin General Hospital from January–June 2013 - Keshina Amalia Mivina Mudia; Ezra Oktaliansah; Ihrul Prianza Prajitno (Althea Medical Journal, 2016)
Background: Musculoskeletal problems of the lower extremities are becoming more frequent lately. This problem usually requires surgery to be dealt quickly . The role of the anesthesiologist is needed to determine which anesthesia technique that has to be performed. Selection of proper anesthesia technique can reduce the incidence of complications . Objective of this study was to determine anesthesia technique selection pattern in patients undergoing orthopedic surgery at Dr. Hasan Sadikin General Hospital from January–June 2013.Methods: A quantitative study with retrospective descriptive method was conducted. This study was carried out from September–October 2013 at Dr. Hasan Sadikin General Hospital Bandung. Medical records were used as a research instrument. Data collection was conducted using total sampling method. There were 228 data of all cases, but only 151 patients who met the inclusion and exclusion criteria.Results: One hundred fifty one patients were identified. Sixty five subjects (43%) were performed under general anesthesia, 83 subjects (55%) under regional anesthesia and 3 subjects (2%) under combination of general-regional anesthesia. Regional anesthesia techniques consisted of spinal anesthesia (29%), epidural anesthesia (64%), combination of spinal-epidural anesthesia (5%), and peripheral nerve block (2%). Conclusions: Regional anesthesia is the most frequently technique used in lower extremities orthopedic surgery, with epidural anesthesia as the most common regional technique used because of all the benefits. [AMJ.2016;3(1):141–6] DOI: 10.15850/amj.v3n1.717